The training of a competent professional in hairdressing and make-art methods (Pedagogy of Higher and Secondary Education, 2012)
Odinets E. The training of a competent professional in hairdressing and make-art methods.This article discusses the concept of «training» and its structure are analyzed different approaches to the concept of «competence of a specialist».
Keywords: training; competence; complex art